Pullulanase: unleashing the power of enzyme with a promising future in the food industry - Naik, Bindu; Kumar, Vijay; Goyal, S. K.; Dutt Tripathi, Abhishek; Mishra, Sadhna; Joakim Saris, Per Erik; Kumar, Akhilesh; Rizwanuddin, Sheikh; Kumar, Vivek; Rustagi, Sarvesh (Frontiers in Bioengineering and Biotechnology, 2023)
Pullulanases are the most important industrial group of enzymes in the family 13 glycosyl hydrolases. They hydrolyze either α-1,6 and α-1,4 or both glycosidic bonds in pullulan as well as other carbohydrates to produce glucose, maltose, and maltotriose syrups, which have important uses in food and other related sectors. However, very less reports are available on pullulanase production from native strains because of low yield issues. In line with the increasing demands for pullulanase, it has become important to search for novel pullulanase-producing microorganisms with high yields. Moreover, high production costs and low yield are major limitations in the industrial production of pullulanase enzymes. The production cost of pullulanase by using the solid-state fermentation (SSF) process can be minimized by selecting agro-industrial waste. This review summarizes the types, sources, production strategies, and potential applications of pullulanase in different food and other related industries. Researchers should focus on fungal strains producing pullulanase for better yield and low production costs by using agro-waste. It will prove a better enzyme in different food processing industries and will surely reduce the cost of products.